2021
DOI: 10.1073/pnas.2012277118
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a small protein factor involved in the coordinated degradation of phycobilisomes in cyanobacteria

Abstract: Phycobilisomes are the major pigment–protein antenna complexes that perform photosynthetic light harvesting in cyanobacteria, rhodophyte, and glaucophyte algae. Up to 50% of the cellular nitrogen can be stored in their giant structures. Accordingly, upon nitrogen depletion, phycobilisomes are rapidly degraded following an intricate genetic program. Here, we describe the role of NblD, a cysteine-rich, small protein in this process in cyanobacteria. Deletion of the nblD gene in the cyanobacterium Synechocystis s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 94 publications
(125 reference statements)
0
19
0
Order By: Relevance
“…Far western blotting was performed as described previously 44,73 with modifications. After electrophoresis, proteins were transferred onto a PVDF membrane.…”
Section: Far Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Far western blotting was performed as described previously 44,73 with modifications. After electrophoresis, proteins were transferred onto a PVDF membrane.…”
Section: Far Western Blottingmentioning
confidence: 99%
“…Synthetic AtpQ peptide, anti-AtpQ antiserum and anti-rabbit IgG antiserum were used for incubation sequentially. Milk powder was omitted in the denaturing/renaturing steps of the blotted membrane as described by Krauspe et al 73 The membrane with renatured proteins was first blocked with 5% milk powder in TBST and then incubated with 3 mg/mL synthetic AtpQ peptide at 4 C overnight. Signals were detected with ECL start western blotting detection reagent (GE Healthcare) on a chemiluminescence imager system (Fusion SL, Vilber Lourmat).…”
Section: Far Western Blottingmentioning
confidence: 99%
“…A hallmark of chlorosis is the rapid proteolytic degradation of phycobiliproteins—the major light-harvesting pigments in red algae and most cyanobacteria—accompanied by cell color change from blue-green to yellow. It has been shown that phycobiliproteins degradation favors the release of soluble amino acids and reduces the intracellular reactive oxygen species level by decreasing the light absorption capability (Forchhammer and Schwarz 2019 , Krauspe et al 2021 ). The current understanding of the chlorotic cells’ regulatory processes depicts the intricate mechanism that modulates ribosomal proteins, RuBisCO (ribulose-1,5-bisphosphate carboxylase-oxygenase) components, central regulators, and metabolic enzymes, as well as hyperphosphorylation of nondegraded phycobiliproteins (Spät et al 2018 , Krauspe et al 2021 a).…”
Section: Pigmentation As a Reflection Of Sab Physiology And Activitymentioning
confidence: 99%
“…It has been shown that phycobiliproteins degradation favors the release of soluble amino acids and reduces the intracellular reactive oxygen species level by decreasing the light absorption capability (Forchhammer and Schwarz 2019 , Krauspe et al 2021 ). The current understanding of the chlorotic cells’ regulatory processes depicts the intricate mechanism that modulates ribosomal proteins, RuBisCO (ribulose-1,5-bisphosphate carboxylase-oxygenase) components, central regulators, and metabolic enzymes, as well as hyperphosphorylation of nondegraded phycobiliproteins (Spät et al 2018 , Krauspe et al 2021 a). The degradation and resynthesis of phycobiliproteins were examined using hyperspectral confocal fluorescence microscopy coupled with single-cell analysis on the basis of the pigment content and localization in live cyanobacterial cells (Murton et al 2017 ).…”
Section: Pigmentation As a Reflection Of Sab Physiology And Activitymentioning
confidence: 99%
“…The traditional method of identifying factors regulating photosynthetic pigments involves culturing many candidate strains on solid media, isolating those in which the pigments are not degraded, and identifying the causal genes ( Collier and Grossman, 1994 ; Karradt et al., 2008 ; Krauspe et al., 2021 ). Most knowledge about pigment degradation, obtained by studying cyanobacteria, has revealed the causative genes regulating phycobilisome levels in cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%